Digital Surface Modelling in Developing Countries Using Spaceborne SAR Techniques - Edwards, Earl Peter Fitz-Gerald (2005)
Topographic databases at the national level, in the form of Digital Surface Models (DSMs), are required for a large number of applications which have been spurred on by the increased use of Geographic Information Systems (GIS). Ground-Based (surveying, GPS, etc.) and traditional airborne approaches to generating topographic information are proving to be time consuming and costly for applications in developing countries. Where these countries are located in the tropical zone, they are affected by the additional problem of cloud cover which could cause delays for almost 75% of the year in obtaining optical imagery. The Caribbean happens to be one such affected territory that is in need of national digital topographic information for its GIS database developments, 3D visualization of landscapes and for use in the digital ortho-rectification of satellite imagery.